BAU LOLON: DARI RITUS KE KEBIJAKAN SEBAGAI STRATEGI ANTI-KORUPSI DALAM PERSPEKTIF ADAT LAMAHOLOT - Lamawuran, Yosef Dionisius; Lamawuran, Yosef; Molan , Kristianus; Kleden , Marianus; Indriyati, Indriyati (Jurnal Agregasi, 2025)
Corruption remains a serious challenge in Indonesian governance, while legal-formal approaches have not been fully effective in curbing corrupt practices, particularly at the local level. This study analyzes how the Bau Lolon ritual, as Lamaholot local wisdom, can be integrated into anti-corruption policies in East Flores Regency. The research employed a qualitative method with a multi-sited ethnographic approach in Adonara, Solor, and West Flores through literature review, in-depth interviews, focus group discussions, and document analysis. Findings show that Bau Lolon functions as a living law that reinforces integrity, honesty, and accountability, thus deserving formal recognition as a public ethical institution complementing positive law. Its integration has the potential to strengthen local anti-corruption policies by embedding moral, social, and cosmic legitimacy rooted in local culture. Theoretically, this study expands the horizon of Indigenous Public Administration by presenting Bau Lolon as a model of hybrid governance, while practically, it recommends traditional oath-taking mechanisms and community-based financial oversight.